"ARMUGONI KHISLAT" IS AN IMPORTANT LITERARY SOURCE (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
This article is focused on studying the anthological collection "Armugoni Khislat" by the representative of Tashkent literary environment, poet, publisher, translator – Sayid Haybatullahkhodi Khislat on the basis of the original source. Peculiar principles for compiling an anthology are determined, it is proved that it is an important literary source.